KEDUDUKAN DAN KEWENANGAN KPK DALAM PERADILAN KONEKSITAS BERDASARKAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 87/PUU-XXI/2023 - Anastasia Lirina; Sujono (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2025)
This research is motivated by issues concerning the authority of the Corruption Eradication Commission (KPK) in handling corruption cases involving both civilian and military jurisdictions, commonly referred to as connectivity cases. The main issues examined are: (a) what is the position and authority of the KPK in handling corruption cases according to the procedural law of connectivity ; and (b) what ratio decidendi and its legal implications of Constitutional Court Decision Number 87/PUU-XXI/2023 on the KPK's authority in handling connectivity corruption cases. The research aims to provide an understanding of the mechanisms for handling connectivity cases, also known as connectivity trials, according to positive law. This includes provisions within Law No. 8 of 1981 concerning the Criminal Procedure Code (KUHAP), Law No. 31 of 1997 concerning Military Courts, Law No. 30 of 2002 concerning the Corruption Eradication Commission (KPK), and Law No. 31 of 1999 concerning the Eradication of Criminal Acts of Corruption (as amended by Law No. 20 of 2001). Furthermore, the research seeks to clarify the position and authority of the KPK following Constitutional Court Decision No. 87/PUU-XXI/2023. Additionally, the research intends to identify the challenges faced by the KPK in handling connectivity cases, such as procedural differences between jurisdictions (civilian and military courts) and institutional coordination. Finally, the research aims to formulate recommendations to enhance the effectiveness of the KPK's authority in handling connectivity corruption cases. The type of legal research employed in this study is normative legal research, utilizing a statute approach, case study approach, and conceptual approach. The research findings indicate that the KPK's position in connectivity cases is not explicitly regulated within the law governing connectivity procedures. However, the KPK, as an investigative institution within the general court system, implicitly possesses the authority to handle connectivity corruption cases based on Article 89 Paragraph (2) of the Criminal Procedure Code (KUHAP) and Article 198 Paragraph (2) of the Military Justice Law. The legal implications of Constitutional Court Decision No. 87/PUU-XXI/2023 affirm that the KPK is authorized to coordinate and control the investigation, inquiry, and prosecution of connectivity corruption cases where law enforcement was initiated or discovered by the KPK.